Long term (>1 year) postpartum glucose tolerance status among Indian women with history of Gestational Diabetes Mellitus (GDM) diagnosed by IADPSG criteria. (August 2018) - Goyal, Alpesh; Gupta, Yashdeep; Kalaivani, Mani; Sankar, M. Jeeva; Kachhawa, Garima; Bhatla, Neerja; Gupta, Nandita; Tandon, Nikhil
Highlights: Long term glucose status in Indian women with GDM history is reported. Diabetes in 10.5% and prediabetes in 47.2% has been found by ADA criteria. Cardiovascular risk factors are deranged significantly. HOMA-IR and insulinogenic index are independent predictors for dysglycemia. Diabetes and prediabetes rates are higher than reported in ATLANTIC-DIP study. Abstract: Aim: To determine prevalence of long term dysglycemia and its risk factors among women with history of GDM diagnosed using IADPSG criteria at a tertiary care hospital in North India. Methods: Women with GDM diagnosed between 2012 and 2016 were invited. Socio-demographic, anthropometric, medical data were collected and 75 gm OGTT with serum insulin estimation, HbA1c and fasting lipid profile were done at the hospital visit. Results: Women (N = 267) were tested at 32.5 (±4.6) years of age and at a median (q25- q75 ) of 20 (12–44) months following the index delivery. Dysglycemia was found in 57.7% by ADA criteria [Diabetes in 10.5% and prediabetes in 47.2%]. Risk factors for cardiovascular disease were significantly more prevalent among these women. On multivariable analysis, HOMA-IR correlated positively, while insulinogenic index correlated negatively with postpartum dysglycemia. Conclusion: This is possibly the first long term (>1 year) glucose tolerance outcome study in South Asian women with history of GDM diagnosed by IADPSG criteria, which demonstrates significantly elevated risk of postpartum dysglycemia. While the IADPSG criteria identify women with a lower future conversion to diabetes compared with previous criteria, prediabetes conversion remains high, thereby offering an opportunity to intervene early and prevent progression to future diabetes.